VJ : the unplugged adventures of MTV's first wave - Blackwood, Nina; Edwards, Gavin, 1968- (Atria Books, 2013)
The original MTV VJs offer a behind-the-scenes oral history of the early years of MTV, circa 1981 to 1985, when it was exploding, reshaping the culture, and forming "the MTV generation."